Data Mining Analysis Using Naive Bayes Algorithm and Knn to Predict Graduation of D3 Students Department of Information Management - Panggabean, Jonas Franky Rudianto; Sirait, Kamson; Naibaho, Frainskoy Rio (the International Journal of Education, Theology, and Humanities, 2022)
In this study, the specific objective of this research is to obtain the results of decisions in predicting students of the informatics management study program whether they can graduate on time for 3 years or more in the specified time and with a minimum GPA of 3.00. Student graduation is one of the Internal Quality Assurance Standards on campus or college. To achieve a decent quality of graduation, a study is needed to be able to predict the graduation rate with predetermined standards, so as to reduce and anticipate problems in the academic field that occur. In this study, data mining methods are used to predict the passing rate and standard GPA with a classification function. The algorithm used in this study is Naïve Bayes and K-NN, the stages used in the application of this research are KDD starting with selecting, preprocessing, transformation, data mining and evaluation/interpretation stages. The final result of this study using the K-NN and Naïve Bayes algorithms is that K-NN produces an accuracy rate of 94.81% and Nave Bayes produces an accuracy rate of 90.49%, so it can be concluded that the K-NN algorithm is better used to predict graduation of D3 students majoring in informatics management.